2013
DOI: 10.1016/j.bmc.2013.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic studies identify mitochondria poisons from botanical dietary supplements—Geranyloxycoumarins from Aegle marmelos

Abstract: Bioassay-guided isolation and subsequent structure elucidation of a Bael tree Aegle marmelos lipid extract yielded two unstable acylated geranyloxycoumarin mixtures (1–2), six geranyloxycoumarins (3–8), (+)-9′-isovaleroxylariciresinol (9), and dehydromarmeline (10). In a T47D cell-based reporter assay, 1 and 2 potently inhibited hypoxia-induced HIF-1 activation (IC50 values 0.18 and 1.10 μg mL−1, respectively). Insufficient material and chemical instability prevented full delineation of the fatty acyl side cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Because auraptene is an inhibitor of mitochondrial complex I [ 11 ], it may be a candidate for the regulation of energy metabolism in RCC. To assess whether mitochondrial oxidative phosphorylation (OXPHOS) in RCC is affected by auraptene, RCC4 cells were incubated with 100 μM auraptene or DMSO (vehicle control) for 24 h and the effects on basal OCR were determined using an XF-24 analyzer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because auraptene is an inhibitor of mitochondrial complex I [ 11 ], it may be a candidate for the regulation of energy metabolism in RCC. To assess whether mitochondrial oxidative phosphorylation (OXPHOS) in RCC is affected by auraptene, RCC4 cells were incubated with 100 μM auraptene or DMSO (vehicle control) for 24 h and the effects on basal OCR were determined using an XF-24 analyzer.…”
Section: Resultsmentioning
confidence: 99%
“…Auraptene, a natural compound initially isolated and purified from citrus fruit, is known as a mitochondrial complex I inhibitor [ 11 ]. In rodent models, auraptene has shown inhibitory effects on mammary and oral carcinogenesis and metastasis of melanoma through modulation of metabolism-related processes, such as hypoxic signaling [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that AUR affects mitochondrial complex I and inhibits mitochondrial respiration in RCC4 renal cell carcinoma cells [8,11]. In this context, effects of AUR on mitochondrial oxygen consumption rate (OCR), shown in Figure 1C,D, are somewhat counterintuitive.…”
Section: Resultsmentioning
confidence: 77%
“…Auraptene (AUR) is a 7-geranyloxylated coumarin isolated from citrus fruit [8]. Natural compounds such as AUR might generally be expected to offer advantages of safety and minimal adverse effects [9]; notably, AUR is able to cross the blood-brain barrier [10].…”
Section: Introductionmentioning
confidence: 99%
“…13,32 Protoliminoids and other constituents found in Bael tree ( Aegle marmelos ) products act as mitochondrial poisons that disrupt the ETC and interfere with global protein translation through an endoplasmic reticulum (ER)-stress activated signaling pathway. 21,33 These A. marmelos studies further indicate that even auraptene (a purported cancer chemopreventative agent) potentially may act as a mitochondrial poison. One of the major challenges for the identification of botanical dietary supplement-induced mitochondrial toxicity is that these products are often consumed in conjunction with clinically approved drugs, which may also produce off-target effects on the mitochondria.…”
Section: Resultsmentioning
confidence: 99%